أهم المشاكل الإنتاجية والتسويقية التي تواجه قطاع الملابس الجاهزة المحلية في مصر - عمارة، ولاء عبدالله إبراهيم; أبو زيد، وفية محمد وجيه عبدالحليم (جامعة كفر الشيخ - كلية التربية النوعية, 2023)
هدف البحث التالي الوقوف على أهم المشاكل الإنتاجية والتسويقية التي تواجه قطاع الملابس الجاهزة المحلية في مصر، وتمثلت مشكلته البحثية في حجم التحديات والعقبات الإنتاجية والتسويقية التي يواجهها هذا القطاع الداخلية منها والخارجية. واعتمدت الدراسة في تحقيق أهدافها على منهج التحليل الوصفي الكمي لمعالجة البيانات الأولية التي تم تجميعها من خلال استبانة تم تصميمها لتحقيق أهداف الدراسة تم توزيعها على عينة ميسرة للباحث بلغ حجمها ٥٤ استبانة تمثل أصحاب المصانع ومديري هذه المصانع. وتوصلت الدراسة لعدد من النتائج الهامة من بينها أن صناعة الملابس في مصر تؤدي دورا هاما في تلبية احتياجات المجتمع ورفع مستوى معيشة الأفراد، كما أنها تساهم في تحقيق التوازن في الميزان التجاري وزيادة موارد الدولة من النقد الأجنبي اللازم لتحقيق برامج التنمية المستدامة. كما تبين من نتائج الدراسة وجود عدة عقبات تواجه قطاع الملابس الجاهزة في مصر بعضها محليا والأخرى دوليا. واستنادا إلى نتائج الدراسة الرئيسية فقد تم صياغة عدد من التوصيات الهامة من بينها ضرورة تفعيل دور الجامعات والمراكز البحثية في البحث والتطوير والتدريب، وتفعيل دور وسائل التواصل الاجتماعي في رفع مستوى الثقافة التسويقية لدى المستهلكين مع ضرورة وضع ضوابط ومعايير صارمة للحد من استيراد ملابس البالات ومكافحة سياسة الإغراق، وخفض تكاليف الإنتاج وتوفير المصادر التمويلية المناسبة، وتبسيط الإجراءات الإدارية والقانونية، وتحسين الجهود الحكومية لتطوير القطاع الصناعي والارتقاء بمستوى خريجي هذا القطاع. This research aimed to understand the significant production and marketing challenges facing the local ready-made clothing sector in Egypt. The research problem lies in the extent of the production and marketing challenges and obstacles this sector faces, both internally and externally. The study adopted a quantitative descriptive analysis method to process the primary data collected through a designed questionnaire to achieve the study's objectives. The questionnaire was distributed to a convenient sample for the researcher, with a total of 54 questionnaires representing the factory owners and their managers. The study reached several important results, among which the clothing industry in Egypt plays a significant role in meeting societal needs and improving individuals' living standards. It also contributes to achieving balance in the trade balance and increasing the state's resources of necessary foreign currency to achieve sustainable development programs. The study's results also showed several obstacles facing the ready-made clothing sector in Egypt, some locally and others internationally. Based on the main results of the study, a number of important recommendations were formulated, including the need to activate the role of universities and research centers in research, development, and training, and the need to activate the role of social media in raising the level of marketing culture among consumers, along with the necessity of setting strict controls and standards to limit the import of second-hand clothes and combat dumping policies, reduce production costs, and provide suitable financial resources.
Keywords: الملابس الجاهزة -- المشكلات الإنتاجية -- الأساليب التسويقية -- مصر